2011
DOI: 10.1128/jb.00377-11
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Streptomyces sp. Strain Tü6071

Abstract: Streptomyces sp. Tü6071 is a soil-dwelling bacterium which has a highly active isoprenoid biosynthesis. Isoprenoids are important precursors for biopharmaceutical molecules such as antibiotics or anticancer agents, e.g., landomycin. Streptomyces sp. Tü6071 produces the industrially important terpene glycosides phenalinolactones, which have antibacterial activity against several Gram-positive bacteria. The availability of the genome sequence of Streptomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…To date, more than 35 genomes of the genus Streptomyces, including Streptomyces coelicolor A3(2) (Bentley et al 2002), Streptomyces avermitilis (Ikeda et al 2003), Streptomyces griseus IFO 13350 (Ohnishi et al 2008), Streptomyces clavuligerus (Song et al 2010), Streptomyces sp. strain Tü6071 (Erxleben et al 2011), Streptomyces cattleya NRRL 8057 (Barbe et al 2011), Streptomyces griseoaurantiacus M045 (Li et al 2011), Streptomyces acidiscabies 84-104 (Huguet-Tapia and Loria 2012), and Streptomyces sp. strain W007 (Qin et al 2012), have been sequenced (http:// www.genomesonline.org/).…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 35 genomes of the genus Streptomyces, including Streptomyces coelicolor A3(2) (Bentley et al 2002), Streptomyces avermitilis (Ikeda et al 2003), Streptomyces griseus IFO 13350 (Ohnishi et al 2008), Streptomyces clavuligerus (Song et al 2010), Streptomyces sp. strain Tü6071 (Erxleben et al 2011), Streptomyces cattleya NRRL 8057 (Barbe et al 2011), Streptomyces griseoaurantiacus M045 (Li et al 2011), Streptomyces acidiscabies 84-104 (Huguet-Tapia and Loria 2012), and Streptomyces sp. strain W007 (Qin et al 2012), have been sequenced (http:// www.genomesonline.org/).…”
Section: Introductionmentioning
confidence: 99%
“…strain Tü6071, sequence accession AFHJ01000000 [94] Bifidobacterium breve UCC2003, sequence accession CP000303 [95] Propionibacterium acnes, sequence accession CP002815 [96] Amycolicicoccus subflavus DQS3-9A1 T , sequence accession CP002786 (chromosome), CP002787 (plasmid pAS9A-1), and CP002788 (plasmid pAS9A-2). [97] Gordonia neofelifaecis NRRL B-59395, sequence accession AEUD01000000 [98] Pseudonocardia dioxanivorans strain CB1190, sequence accession NC_015312-4 and CP002595-7 [99] Bifidobacterium longum subsp.…”
Section: Tenericutesmentioning
confidence: 99%
“…Whole genome analysis of Streptomyces sp. Tü6071 revealed that genes involved in the MEP pathway are located upstream of the phenalinolactone biosynthetic gene cluster . To the best of our knowledge, the only genetic work in Streptomyces sp.…”
mentioning
confidence: 99%
“…To the best of our knowledge, the only genetic work in Streptomyces sp. Tü6071 up to now has been the characterization of the phenalinolactone gene cluster and the sequencing of its genome …”
mentioning
confidence: 99%
See 1 more Smart Citation